EFEKTIVITAS BIMBINGAN PRANIKAH DALAM MENCIPTAKAN KEHARMONISAN KELUARGA DI KANTOR URUSAN AGAMA KECAMATAN MOJOWARNO KABUPATEN JOMBANG TAHUN 2023 - Ainun Salsabila; Ahmad Faruq (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The Ministry of Religion, through the Decree of the Director General of Islamic Community Guidance Number 172 of 2022, instructed that every prospective bride and groom who are going to get married must first follow marriage guidance as a step in creating a sakinah, mawaddah and rahmah family. Based on this background, the main problems are: 1). How effective is the implementation of premarital marriage guidance at the Mojowarno District KUA? 2). How to analyze the implementation of premarital guidance in creating family harmony for bridal couples in the KUA, Mojowarno District? This research, which can be categorized as field research, can also be considered as a broad approach to qualitative research or as a method for collecting qualitative data. This research was carried out by coming directly to the research location, namely the Religious Affairs Office (KUA) Mojowarno District, Jombang Regency.Based on the results of the research conducted, the author concludes: First, the implementation of premarital marriage guidance at the Mojowarno District KUA has been effective in accordance with the technical instructions for implementing marriage guidance, clarity of objectives to be achieved, and fulfillment of intrastructure needs. Second, after following the marriage guidance process there is a positive influence on the family harmony of the bridal couple. Mentally and scientifically, participants become more mature in living their married life, they become wiser in responding to problems in their domestic life.